AGRICULTURAL EDUCATION AND RESTRUCTURING - Ibrahim, Fati Jalo; Farauta, K. G. (Sokoto Educational Review, 2015)
Increasing awareness of the important of vocational agricultural education has drive various regimes in government and education to embark on several review of agricultural curriculum at both secondary and tertiary institutions and as well as a good and profitable way of life when properly practiced. Unfortunately, in spite of the various efforts by government and other stake holders, it had been widely reported that agriculture in schools had been a failure. Agricultural education and restructuring are the focus of this study and the components for restructuring agricultural education programs are general agricultural education, linkage of agricultural education to the society and small agricultural business management and entrepreneurial training. The study also discussed the need for restructuring agricultural education, objectives of agricultural education, agricultural education/learning, shortfalls in current secondary and tertiary agricultural education, recommendations and suggestions were made in achieving sustainable development through vocational agricultural education.